2014
DOI: 10.1152/ajprenal.00367.2014
|View full text |Cite
|
Sign up to set email alerts
|

Collecting duct-specific knockout of renin attenuates angiotensin II-induced hypertension

Abstract: The physiological and pathophysiological significance of collecting duct (CD)-derived renin, particularly as it relates to blood pressure (BP) regulation, is unknown. To address this question, we generated CD-specific renin knockout (KO) mice and examined BP and renal salt and water excretion. Mice containing loxP-flanked exon 1 of the renin gene were crossed with mice transgenic for aquaporin-2-Cre recombinase to achieve CD-specific renin KO. Compared with controls, CD renin KO mice had 70% lower medullary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 25 publications
10
66
0
Order By: Relevance
“…A recent study showed that deletion of renin in the collecting duct principal cells (using an aquaporin 2-Cre mouse) did not affect blood pressure, even varying Na intake (16). However, those mice had an attenuated response to ANG II-induced hypertension (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that deletion of renin in the collecting duct principal cells (using an aquaporin 2-Cre mouse) did not affect blood pressure, even varying Na intake (16). However, those mice had an attenuated response to ANG II-induced hypertension (16).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that deletion of renin in the collecting duct principal cells (using an aquaporin 2-Cre mouse) did not affect blood pressure, even varying Na intake (16). However, those mice had an attenuated response to ANG II-induced hypertension (16). Whether renin expression in the collecting duct plays a role during pathological processes still remains to be investigated, but in our study, deletion of renin in the tubular compartment did not result in any discernible morphological or physiological changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, weak renin staining was only observed in the juxtaglomerular apparatus of normal kidneys ( Figure 5F, open arrow), whereas renin was predominantly induced in renal tubular epithelial cells after kidney injury ( Figure 5F, solid arrows), consistent with previous observations. [31][32][33] We further investigated the effects of exogenous Wnt1 on matrix gene expression and renal fibrotic lesions after AKI. As shown in Figure 6, A-D, in vivo expression of exogenous Wnt1 significantly induced the mRNA expression of a-smooth muscle actin (a-SMA), fibronectin, and types I and III collagens in the kidneys after IRI as shown by qRT-PCR analyses.…”
Section: In Vivo Expression Of Wnt Augments Renal Fibrosis After Akimentioning
confidence: 99%
“…[10][11][12][13] The involvement of an intrarenal renin-angiotensin system now seems to be an important component of the pathophysiological mechanisms involved in essential hypertension. [12][13][14][15][16][17][18][19] In the present review, I will first provide a brief summary of my earlier contributions to the hypertension field, these having been addressed in more detail in a review arising from my Lewis K. Dahl Memorial Lecture in 2010. 20 I will then review my more recent research, which has involved the determination of alterations in gene expression at the transcriptome-wide level in hypertension and the pivotal mechanistic insights this work has provided, especially an intriguing mechanism controlling intrarenal renin.…”
mentioning
confidence: 99%